2013
DOI: 10.1200/jco.2013.31.4_suppl.242
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective review of chemotherapy for patients with small bowel adenocarcinoma in British Columbia.

Abstract: Background: Small bowel adenocarcinoma (SBA) is associated with a poor prognosis. It is an uncommon malignancy and therefore difficult to study. Randomized phase III trials are not available to guide best approaches. The Provincial Cancer Registry of the British Columbia Cancer Agency contains long-term data on patients with SBA. The authors analyzed characteristics and treatment outcomes for SBA patients diagnosed between 1990 and 2008. Material and methods: Charts of 150 patients with a histological diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…There is a need for high-level evidence studies to better clarify the role of adjuvant chemotherapy in the context of small bowel adenocarcinoma. 18 For jejunal and ileal tumors, curative surgery (R0) consists of a wide resection with free cancer margins, associated with regional lymphadenectomy, similar to colonic adenocarcinomas. 6 Video-laparoscopy and its application in cancer surgery has been gaining greater acceptance among surgeons and consolidating as an effective and safe approach for the surgical treatment of malignant tumors of the small intestine.…”
Section: Discussionmentioning
confidence: 99%
“…There is a need for high-level evidence studies to better clarify the role of adjuvant chemotherapy in the context of small bowel adenocarcinoma. 18 For jejunal and ileal tumors, curative surgery (R0) consists of a wide resection with free cancer margins, associated with regional lymphadenectomy, similar to colonic adenocarcinomas. 6 Video-laparoscopy and its application in cancer surgery has been gaining greater acceptance among surgeons and consolidating as an effective and safe approach for the surgical treatment of malignant tumors of the small intestine.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the rarity of the disease, most data on palliative chemotherapy in SBA are derived from phase II trials and retrospective series of mainly high‐volume or tertiary medical centres 5–7 . These studies have demonstrated that chemotherapy prolongs overall survival in patients with metastatic SBA 4–15 . However, in the absence of randomised controlled trials, a standard chemotherapeutical regimen has not been defined.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] These studies have demonstrated that chemotherapy prolongs overall survival in patients with metastatic SBA. [4][5][6][7][8][9][10][11][12][13][14][15] However, in the absence of randomised controlled trials, a standard chemotherapeutical regimen has not been defined. Patients are usually treated with chemotherapeutical regimens which have been extrapolated from other gastrointestinal cancers.…”
Section: Introductionmentioning
confidence: 99%